Perbedaan Pengaruh Metode Simulasi Game dengan Metode Audio Visual Terhadap Peningkatan Pengetahuan Kesehatan Reproduksi Remaja Putri di SMPN 1 Kecamatan Pelangiran Kabupaten Indragiri Hilir - Nani Hariyani; Rifa Yanti; Hirza Rahmita; Nurhidaya Fitria (Universitas Pahlawan Tuanku Tambusai, 2025)
In Indonesia, reproductive health education is still considered taboo, so many teenagers do not know the dangers of engaging in risky sexual behavior and its impacts. The results of interview in 10 female teenagers at SMPN 1 is 7 of whom stated the importance of conducting counseling on health education because learning in schools about reproductive health is still lacking. Objective: to determine the difference in the effect of game simulation method with audio visual method on inluence reproductive health knowledge of female adolescents at SMPN 1 Pelangiran District, Indragiri Hilir Regency. Method: the research design is true experimental pre test-post test control group design. The population of this study was all female adolescents at SMPN 1 Pelangiran District as many as 140 respondents and the sample used was 28 people. The sample was divided into 2 groups, namely 14 people using the game simulation method and 14 people using the audio visual method with sample selection using the simple random sampling technique. The results of Wilcoxon test, the average pre-post value in the game simulation method group (8.36 : 9.50) with a p value of 0.02 <0.05 and the audio-visual method group is (8.50: 8.93) with a p value of 0.03 <0.05. The results of the Mann Whitney test obtained a p value of 0.04 <0.05 indicating that there is a significant difference in influence reproductive health knowledge between health promotion using game simulation and audio visual.